2012
DOI: 10.3899/jrheum.120370
|View full text |Cite
|
Sign up to set email alerts
|

RANK-RANKL-OPG in Hemophilic Arthropathy: From Clinical and Imaging Diagnosis to Histopathology

Abstract: In hemophilic arthropathy, the synovium highly expressed RANK and RANKL, whereas OPG immunopositivity decreased, suggesting an osteoclastic activation. Low tissue expression of OPG paralleled the serum levels of this protein and the severity of hemophilic arthropathy assessed by ultrasonography, Pettersson, and WFH orthopedic joint scale scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 34 publications
7
42
0
Order By: Relevance
“…They concluded that low tissue expression of OPG paralleled its serum levels and the severity of hemophilic arthropathy (Melchiorre et al, 2012). .These data are consistent with a randomized study showing that the prophylaxis with recombinant Factor VIII prevents joint damages in young haemophilic patients (Manco-Johnson et al 2007), possibly through a decrease in osteoclastogenesis.…”
Section: Rankl and Trail: Ligands From The Tnf Familysupporting
confidence: 77%
“…They concluded that low tissue expression of OPG paralleled its serum levels and the severity of hemophilic arthropathy (Melchiorre et al, 2012). .These data are consistent with a randomized study showing that the prophylaxis with recombinant Factor VIII prevents joint damages in young haemophilic patients (Manco-Johnson et al 2007), possibly through a decrease in osteoclastogenesis.…”
Section: Rankl and Trail: Ligands From The Tnf Familysupporting
confidence: 77%
“…33,34 An upregulation of the nuclear factor-kB pathway, which is induced by IL-1b, has been emphasized in hemophilic mice upon joint bleeding 34 and in synovial tissue of patients with hemophilic arthropathy. 35 In experimental arthritis, blocking IL-1 prevents cartilage damage upon inflammation 36,37 as is also observed in a posttraumatic osteoarthritis model. 38 Therapeutic efficacy of IL-1RA is demonstrated in hand osteoarthritis 39 and in 2 cases suffering from another form of ironinduced arthropathy in case of hemochromatosis.…”
Section: 28mentioning
confidence: 85%
“…[7][8][9] In a previous study, we provided evidence of a strong correlation between the severity of arthropathy in HA patients and the expression of the RANK/RANKL/OPG triad in synovial tissue, as well as circulating levels of sRANKL and OPG. 19 Therefore, in the present work we investigated for the first time the possible differences in the RANK/RANKL/OPG triad between HA and HB patients.…”
Section: Discussionmentioning
confidence: 99%
“…19 Synovial samples from 16 osteoarthritis (OA) patients were included as controls. Each synovial specimen was cut into small pieces, fixed in 10% buffered formalin and, after standard processing, embedded in paraffin wax and used for light microscopy.…”
Section: Synovial Biopsy Samples and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation